Educator Satisfaction Using LMS with ICT Infrastructure as a Mediation Variable - Rokhimah, Siti; Sirait, Afni (RSF Conference Series: Business, Management and Social Sciences, 2021)
The use of technology during the COVID-19 pandemic is very helpful in providing teaching materials to students. Two-way and collaborative interactions can be created with a dynamic learning platform such as an LMS. This study aims to analyze user satisfaction, especially with educators in using LMS with the support of ICT Infrastructure. Satisfaction is seen in terms of usefulness (usability), Ease of Use (Ease of use), and Accessibility (Access Range). Respondents in this study were 55 respondents. The data was collected using an online google form questionnaire which was then tested for validity, reliability, and model fit using the War PLS 7.0 analysis tool. The test results show that usefulness has a significant impact on user satisfaction mediated by ICT Infrastructure (with a path coefficient value of 0.524, p-value <0.001). Ease of Use has no significant impact on user satisfaction mediated by ICT Infrastructure (with a path coefficient value of 0.150 with a p-value of 0.122). Accessibility has a significant impact on user satisfaction in mediation with ICT Infrastructure (with a coefficient value of 0.309 with p-value <0.001). The fit model is tested with a VIF value of 1.670 and a GoF value of 0.586. The limitations of this study are that the sample needs to be increased, and exogenous variables need to be added to expand knowledge.